Factors associated with seroimmunity against tick borne encephalitis virus 10 years after booster vaccination - Paulke-Korinek, Maria; Kundi, Michael; Laaber, Brigitte; Brodtraeger, Natascha; Seidl-Friedrich, Claudia; Wiedermann, Ursula; Kollaritsch, Herwig (Vaccine, 2013)
► Tick borne encephalitis antibody titers were assessed in 178 and 183 subjects 8 and 10 years post-booster. ► Cumulative seroprotection rates were 86.8% and 77.3% 8 and 10 years post-booster. ► Antibody levels were significantly lower in subjects starting at the age of 50 years. ► Antibody levels were significantly higher in subjects reporting any kind of allergy. ► A single booster dose was highly effective in subjects who lost protective antibody titers 10 years post-booster. In a sample of originally 430 healthy adults (18–84 years of age) with documented basic and booster immunization against tick borne encephalitis, cumulative seroprotection rates 8 (n=178) and 10 years (n=183) after the last booster dose were 86.8% and 77.3% according to the neutralization test, respectively. In subjects aged 50 years and older, antibody titers were significantly lower compared to subjects younger than 50 years. History of any allergy but not previous exposure to other flaviviral antigens was associated with higher neutralization titers. In subjects with waning immunity, a single booster dose induced a strong anamnestic antibody response.